Pengaruh Kombinasi Numbered Heads Together dan Student Teams Achievement Divisions Terhadap Minat Belajar Siswa dalam pembelajaran Pendidikan Agama Islam Di SMK Perpajakan Riau - Sainal Nasution; Idris Harun; Zaitun Zaitun (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2022)
Abstrak: The aimed of this research was to know the contradiction of the students' interest in PAI learning through NHT and STAD combination between experimental class and control class. This research was a field research with quasy experimental design. Furthermore, a questionnaire and observation were used in the data collection techique. There were 54 students as the samples of this research. There were 28 students in experimental class and 26 students in control class.  Then, in analysing the data, the researcher used independent sample t test. The result showed that there was significant difference of experimental and control class through NHT and STAD combination . It can be seen that t-count was higher than t-table (2.515>2.007) and  the significance value lower than 0.05 (0.0015<0.05). Therefore , Ho was rejected and Ha was accepted. Then, there was difference mean score of experimental and control class at SMK Perpajakan Riau, the experimental class was higher (94,25) than control class (86.23).TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//